Interculturalism in Education - Osman Emin, Biljana Krsteska Papik, Sonaj Bilal (The publication of this Handbook was made possible by the support of the OSCE Mission in Kosovo., 2023)
Intercultural education is a contemporary educational trend and tendency, but also a global constructive response to intense migration processes and diversity in social communities that reflect cultural, linguistic and ethnic heterogeneity.